DEVELOPMENT AND EVALUATION OF HERBAL ANTIAGING CREAM FORMULATION CONTAINING ANNONA SQUAMOSA LEAF EXTRACT - MAHAWAR, VANDANA; PATIDAR, KALPANA; JOSHI, NEELAM (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The aim of this research article is to develop and evaluate herbal antiaging cream using Annona squamosa leaf extract because of its antioxidant potential. Method: Free radical scavenging activity of Annona squamosa aqueous was determined by DPPH method. 0.5 ml of each solution of concentration of sample was added to 3 ml of 0.004% ethanolic DPPH free radical solution. After 30 minutes the absorbance of the preparations were taken at 517 nm by a UV spectrophotometer which was compared with the corresponding absorbance of standard ascorbic acid. The qualitative phytochemical analysis of Annona squamosa (custard apple) leaf extract shows the presence of flavonoids, tannins, alkaloids and phenols and absence of terpenoids and steroids Results: Formulation A3 shows good DPPH scavenging activity as compare to formulation A1 and A2 and ascorbic acid. Formulation A3 is stable for 3 months. Conclusion: Due to high antioxidant values of Annona squamosa it is concluded that it is possible to develop anti-aging cream using aqueous extract of Annona squamosa leaf.